UNIVERSAL MODELS OF POLYSEMOUS NOUNS IN ENGLISH AND GEORGIAN LANGUAGES - Vardidze, Tinatin (Online Journal of Humanities ETAGTSU, 2020)
This paper presents the results of a comparative study of polysemous words to reveal universal models of nouns in the English and Georgian languages. The study examines the models of nouns denoting the body parts (hand, head), facial parts (eye, mouth), as well as the names of the internal organs (heart, brain) through comparing them with the same group words in the Georgian language. The research through the methodology of definitional analysis, contextual analysis and corpus analysis, revealed that these noun groups represent the same type of model that professor Tinatin Margalitadze named as solar model (Margalitadze, 2008). I present the sub models of the mentioned solar model; I further distinguished a long-ray solar model and a shortray solar model. The research is part of my thesis on universal models of polysemous nouns in the English and Georgian Languages. In this paper I will discuss the example of the comparative study of the noun “eye” to present the results of the research. Full Text (PDF)